2019
DOI: 10.1038/s41467-019-08954-z
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation strengthening in an ultralight magnesium alloy

Abstract: Body-centred cubic magnesium-lithium-aluminium-base alloys are the lightest of all the structural alloys, with recently developed alloy compositions showing a unique multi-dimensional property profile. By hitherto unrecognised mechanisms, such alloys also exhibit exceptional immediate strengthening after solution treatment and water quenching, but strength eventually decreases during prolonged low temperature ageing. We show that such phenomena are due to the precipitation of semi-coherent D0 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(48 citation statements)
references
References 27 publications
(25 reference statements)
1
47
0
Order By: Relevance
“…The widely accepted understanding suggests that precipitates do not prevent twin nucleation, but that they might strongly interfere with the process of twin growth [24,75,81,[86][87][88]. For instance, Stanford et al [89] observed a higher density of small twins in age-hardened Mg-Zn alloys than in precipitate-free samples.…”
Section: Precipitation Effectsmentioning
confidence: 99%
“…The widely accepted understanding suggests that precipitates do not prevent twin nucleation, but that they might strongly interfere with the process of twin growth [24,75,81,[86][87][88]. For instance, Stanford et al [89] observed a higher density of small twins in age-hardened Mg-Zn alloys than in precipitate-free samples.…”
Section: Precipitation Effectsmentioning
confidence: 99%
“…In recent years, many series of magnesium alloys have been reported. For example, magnesium alloys with different rare earth elements [6,7], magnesium alloys with different elements (such as Al, Zn, Sn, Mn, and Li) have exhibited excellent properties [8][9][10]. The mechanical properties of the magnesium alloys can be strengthened by plastic deformation processing such as extrusion or rolling [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Although there exists a plethora of studies on the processing, microstructure and physical properties of Mg-based alloys (see e.g., [9][10][11][12][13][14][15][16][17]), to date, there remains a limited reporting, characterisation and rationalisation of processing-structure-properties relationships for AM produced Mg alloys [18][19][20]. In part this is because the production of Mg-based alloys by AM has been considered complicated, owing to a range of factors that could include: safety concerns associated with the reactive nature of Mg powder; the superheating and boiling / evaporation of Mg via interaction with laser based methods; a tendency for ignition in the presence of common environments (Mg can burn under air or N 2 ), and even supply chain issues for Mg powder of suitable size and composition (relevant to powder based AM).…”
Section: Introductionmentioning
confidence: 99%